2015
DOI: 10.1080/10291954.2015.1006482
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of corporate governance and company performance: a South African perspective

Abstract: This study examines the relationship between corporate governance mechanisms and company performance as measured by economic value added (EVA), return on assets (ROA) and Tobin's Q. A multiple regression model is used to compare the association between corporate governance mechanisms and company performance for 158 companies listed on the JSE Securities Exchange (formerly known as the Johannesburg Stock Exchange) for the year 2012. We report four main results. First, board size is found to be negatively and si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 42 publications
(83 reference statements)
3
13
1
2
Order By: Relevance
“…Similar to the studies of Mohammed, Che-Ahmad and Aljaaidi (2012) and Pamburai et al (2015), the fact that the correlation coefficients are below the 0.8 threshold indicates that multicollinearity is not a problem in this study.…”
Section: Assumption Of Multicollinearitysupporting
confidence: 89%
See 3 more Smart Citations
“…Similar to the studies of Mohammed, Che-Ahmad and Aljaaidi (2012) and Pamburai et al (2015), the fact that the correlation coefficients are below the 0.8 threshold indicates that multicollinearity is not a problem in this study.…”
Section: Assumption Of Multicollinearitysupporting
confidence: 89%
“…Further, similar to the studies of Muchemwa, Padia and Callaghan (2016), Pamburai et al (2015) and Rodriguez-Fernandez, Fernandez-Alonso and Rodriguez-Rodriguez (2014), in addition to the correlation matrix, this study also assesses the variance inflation factors to check the level of multicollinearity for each dependent variable against all six independent variables. Chatterjee and Hadi (2012) posit that a value of variance inflation factors larger than 10 should be considered an indication of the presence of multicollinearity.…”
Section: Assumption Of Multicollinearitymentioning
confidence: 89%
See 2 more Smart Citations
“…The recent debate on the performance of insurance firm will for a long time remain an area of interesting research. The scandals in the early 1990's has exposed many multinational firms in the United Kingdom and United States with a high-profile corporate scandals, unexpected corporate failures, unprofessional behaviours by the Chief Executive Officer (CEO) and management (Adegbite, 2015;Al-matari, 2014;Ehikioya, 2009;Harvey Pamburai, Chamisa, Abdulla & Smith, 2015;Rossi, Nerico&Capasso, 2015; Nuhu& Ahmad, 2017; Samaduzzaman, Zaman &Quazi, 2015). It has been suggested that the scandals at Enron, WorldCom, Qwest, Tyco and other corporate entities in the US resulted in a loss of more than USD 7 trillion of investors' funds (Donaldson, 2003;Global Issue, 2009;Lawal, 2012).…”
Section: Introductionmentioning
confidence: 99%